2019
DOI: 10.1080/20507828.2019.1637067
|View full text |Cite
|
Sign up to set email alerts
|

Smart as a Global Vision? Exploring Smart in Local District Development Projects

Abstract: This article studies local enactments of "smart" in and through visions of six smart district development projects. We show that smart cities' framings of the future are inevitably diverse, emerging from local assemblages consisting of a wide array of heterogeneous elements that translate global imaginaries of the smart city to meet local specificities, needs and agendas. We demonstrate that visions may describe the process of district planning and design, the materiality of the envisioned district and the gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…First, with regard to the role of knowledge politics across all stages of such projects, we observed that choices with important future implications for the potential effects on the socio-material urban fabric of a smart experiment are continuously made, for example with regard to problem formulations, methods of data collection and analysis, reporting and communication, critique and validation, translation between settings and circulation, and applications in institutional practice and decision-making (de Hoop 2020; also see Chilvers and Kearnes 2016). However, in the projects that we observed, open deliberation on these issues only happened occasionally, and often in the form of a specific event, like a kick-off brainstorm meeting with multiple stakeholders, as we have seen in the Utrecht Slimcity project (de Hoop et al 2019), or with regard to specific aspects of the project's and technology's design, as we have seen in the GammaSense project in the Netherlands ( . Instead, we argue that deliberation should be a continuous endeavor and on the agenda of multiple moments of interaction before, during and after the project.…”
Section: Engaging With Politics Of Time: Whenmentioning
confidence: 85%
See 3 more Smart Citations
“…First, with regard to the role of knowledge politics across all stages of such projects, we observed that choices with important future implications for the potential effects on the socio-material urban fabric of a smart experiment are continuously made, for example with regard to problem formulations, methods of data collection and analysis, reporting and communication, critique and validation, translation between settings and circulation, and applications in institutional practice and decision-making (de Hoop 2020; also see Chilvers and Kearnes 2016). However, in the projects that we observed, open deliberation on these issues only happened occasionally, and often in the form of a specific event, like a kick-off brainstorm meeting with multiple stakeholders, as we have seen in the Utrecht Slimcity project (de Hoop et al 2019), or with regard to specific aspects of the project's and technology's design, as we have seen in the GammaSense project in the Netherlands ( . Instead, we argue that deliberation should be a continuous endeavor and on the agenda of multiple moments of interaction before, during and after the project.…”
Section: Engaging With Politics Of Time: Whenmentioning
confidence: 85%
“…Inclusive multi-stakeholder engagement requires resources, time, and the motivation to persevere, especially when difficulties or unexpected events arise (Evans et al 2019). For example, in the Slim City project in Utrecht (de Hoop et al 2019), outcomes were expected within a predefined time-frame of 10 weeks, which led to conflicts between actors who wished to speed up the process, typically those that had to report back to their organizations, and actors who felt the need for more in-depth deliberation. Hence, we propose that an active effort should be made on the part of major players such as government authorities, company representatives etc., to include people and perspectives that are currently being de Hoop et al Urban Transformations (2022) 4:6 excluded.…”
Section: Engaging With Politics Of Inclusion: Whomentioning
confidence: 99%
See 2 more Smart Citations